Construction Of Commercial Contracts: Strict Law Or Common Sense - Lord Clyde, The Right Honourable (Journal of Malaysian and Comparative Law, 2000)
Text of the Fifteenth Sultan Azlan Shah Law Lecture (organised by the Faculty of Law, University of Malaya, Malaysia Airlines and The British Council) delivered by the Rt Hon Lord Clyde, PC, on 13 November 2000 in presence of His Royal Highness, Sultan Azlan Muhibbuddin Shah, the Sultan of Perak Darul Bridzuan and His Royal Highness, Raja Nazrin Shah.